2013
DOI: 10.1002/rcm.6713
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of poly(amidoamine) dendrimers in urine by liquid chromatography/electrospray ionization hybrid quadrupole linear ion trap mass spectrometry

Abstract: The developed method has demonstrated a capability for the identification and quantification of PAMAM dendrimer nanoparticles in a complex liquid matrix. The use of an LC/ESI-QqLIT-MS system, of modest m/z range and unit resolution, offers an alternative in the analysis of lower generation PAMAM dendrimers between mass analyzers of higher resolution and the conventional LC-UV method that is commonly applied for dendrimer quantification, but which lacks sufficient identification capacity. Copyright © 2013 John … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Using a 650 nm LED as the light source, the LODs were 0.5, 1.2, and 2.6 μg/mL for PAMAMs G1.0, G2.0, and G3.0, respectively, with recoveries between 91.13% and 97.01% for urine samples. The detection sensitivity of the method was comparable to that of HPLC‐fluorimetry [45] and HPLC‐MS [46]. Moreover, because the PAMAMs have multiple terminal amines (e.g., the numbers of terminal amine groups on PAMAMs G1.0, G2.0, and G3.0 are 8, 16, and 32, respectively), the PAMAM‐AuNP interaction showed good selectivity.…”
Section: Colorimetric Detectionmentioning
confidence: 90%
“…Using a 650 nm LED as the light source, the LODs were 0.5, 1.2, and 2.6 μg/mL for PAMAMs G1.0, G2.0, and G3.0, respectively, with recoveries between 91.13% and 97.01% for urine samples. The detection sensitivity of the method was comparable to that of HPLC‐fluorimetry [45] and HPLC‐MS [46]. Moreover, because the PAMAMs have multiple terminal amines (e.g., the numbers of terminal amine groups on PAMAMs G1.0, G2.0, and G3.0 are 8, 16, and 32, respectively), the PAMAM‐AuNP interaction showed good selectivity.…”
Section: Colorimetric Detectionmentioning
confidence: 90%
“…It was found that both batches are highly similar containing charge mass values of the characteristic fragments of the G0, G1, G2 and G3 dendrimers at the same relative intensity (Figure S3). The identification of the most abundant fragments of OS-PAMAM will be useful for biomedical applications such as for determining the elimination pathways in pharmacokinetic surveys using urine as the main elimination via ( [26,56,57].…”
Section: Structural Characterization By Ms-msmentioning
confidence: 99%